Universidade em tempos de pandemia: um estudo sobre os impactos da adoção do teletrabalho na percepção de servidores públicos - Araújo, Thiego Santos de (2020)
To contain the pandemic of the new coronavirus (covid-19), Brazilian public institutions have implemented drastic restrictions on public or social life, which have resulted in the paralysis of classroom administrative and academic activities across their higher education network. In this sense, with the objective of reducing the crowding of people, and thus helping to contain the spread of the disease, the Federal University of Rio Grande do Norte (UFRN), authorized remote work for its servers and suspended the face-to-face service to the public administrative and academic units. Although teleworking in public administration was already a reality, it was only in 2020, during the pandemic of the new coronavirus, that most Brazilian public universities started to adopt it as a way of working. Knowing that this modality can bring a series of consequences for the worker, the present research carried out a case study to identify the advantages and disadvantages of the adoption of telework, during the pandemic of the new coronavirus (covid-19), in the perception of the technical servers -administratives of the Faculty of Health Sciences of Trairi (FACISA/UFRN). This is a descriptive research with a quantitative approach and with a cross-sectional design, which used as a tool a questionnaire applied to administrative technicians from FACISA/UFRN who started teleworking during the coronavirus pandemic, addressing several issues related to teleworking. The results of the research show that, in the perception of FACISA servers, UFRN's option for the adoption of teleworking during the coronavirus pandemic provided numerous advantages, in which the following stand out: greater autonomy at work, greater flexibility in working hours and relationships, reduction in time, stress and travel expenses, cost reduction with clothing, possibility of having meals at home, greater interaction with the family, greater privacy, possibility of doing other work on their own, improvement in the quality of personal life and at work, in addition to the feeling of greater security that may be related to the lower risks linked to urban violence and traffic, in addition to less exposure to the coronavirus. As for the negative aspects, the research identified as main disadvantages the greater distraction with home activities, the decrease in the quality of work, the fear of losing work benefits, the greater professional isolation, technological infrastructure problems and the lack of specific training. It is hoped that the results obtained will increase knowledge about this type of work and provide subsidies for the strategic planning of public universities that intend to implement the teleworking regime in the post-pandemic period or improve an existing program.